Effect of high-volume ultrafine palm oil fuel ash on the engineering and transport properties of concrete - Hamada, Hussein M.; Al-attar, Alya’a A.; Fadzil, Mat Yahaya; Khairunisa, Muthusamy; Tayeh, Bassam A.; Humada, Ali M. (Elsevier Ltd, 2020)
Palm oil fuel ash (POFA) is a by-product in palm oil manufacturing and is currently disposed to open areas and landfills without any previous treatment, thereby causing environment pollution. The use of small-particle-sized ground POFA to prepare ultrafine POFA (UPOFA) is a suitable method to improve its characteristics as a supplementary cementitious material. Although high-volume POFA exhibits reduced mechanical properties in the early ages, heat treatment and further grinding reduce its carbon content and increase its pozzolanic activity. In this study, UPOFA was used to minimise the cement content in concrete mix. Cement was replaced with UPOFA at 0 %, 20 %, 40 %, 60 % and 80 % ratios to produce green concrete. Results revealed that the UPOFA showed remarkable improvement in concrete strength, especially with 20 % and 40 % substitution levels. By contrast, the compressive strength reduced at high replacement levels to be 34.5 MPa at 28 days. The water absorption of concrete containing UPOFA is considerably reduced, thus improving the concrete’s durability.